Previously Derived Host Gene Expression Classifiers Identify Bacterial and Viral Etiologies of Acute Febrile Respiratory Illness in a South Asian Population. (26th May 2020) - Tillekeratne, L Gayani; Suchindran, Sunil; Ko, Emily R; Petzold, Elizabeth A; Bodinayake, Champica K; Nagahawatte, Ajith; Devasiri, Vasantha; Kurukulasooriya, Ruvini; Nicholson, Bradly P; McClain, Micah T; Burke, Thomas W; Tsalik, Ephraim L; et al.
Abstract: Background: Pathogen-based diagnostics for acute respiratory infection (ARI) have limited ability to detect etiology of illness. We previously showed that peripheral blood-based host gene expression classifiers accurately identify bacterial and viral ARI in cohorts of European and African descent. We determined classifier performance in a South Asian cohort. Methods: Patients ≥15 years with fever and respiratory symptoms were enrolled in Sri Lanka. Comprehensive pathogen-based testing was performed. Peripheral blood ribonucleic acid was sequenced and previously developed signatures were applied: a pan-viral classifier (viral vs nonviral) and an ARI classifier (bacterial vs viral vs noninfectious). Results: Ribonucleic acid sequencing was performed in 79 subjects: 58 viral infections (36 influenza, 22 dengue) and 21 bacterial infections (10 leptospirosis, 11 scrub typhus). The pan-viral classifier had an overall classification accuracy of 95%. The ARI classifier had an overall classification accuracy of 94%, with sensitivity and specificity of 91% and 95%, respectively, for bacterial infection. The sensitivity and specificity of C-reactive protein (>10 mg/L) and procalcitonin (>0.25 ng/mL) for bacterial infection were 100% and 34%, and 100% and 41%, respectively. Conclusions: Previously derived gene expression classifiers had high predictive accuracy at distinguishing viral and bacterial infection in South Asian patients with ARI caused by typical and atypical pathogens. Abstract : Host biomarkers can identify bacterial versus viral acute respiratory infection (ARI). Previously, we derived host gene expression classifiers that accurately identify bacterial versus viral ARI. Here, we show that our classifiers had high predictive accuracy in a South Asian cohort.